Analysis of protein content of deffated black soldier fly (BSF) maggot flour with variations in drying temperature - Ari Susandy Sanjaya; Tera Nurjanah; Christiano Johnson; Rudy Agung Nugroho; Dudi Adi Firmansyah; Arief C. Wibowo (Konversi, 2025)
This study aims to determine the protein content in maggot flour based on differences in drying temperatures. Maggots or black soldier fly larvae are currently known for their high protein content and have the potential as a substitute for animal feed. The flouring process is carried out by drying the maggots and then extracting the drying results to obtain flour. This study was conducted by drying maggots with temperature variations of 60 ℃, 90 ℃, and 120 ℃ for 3 hours. Dried maggots were also used with a different process, namely the roasting method as a comparison. The results of the study showed that the higher the drying temperature, the more flour would be produced during the extraction process. Protein content testing was carried out using the Kjeldhal method. The results of this study showed that with a drying temperature of 120 ℃, flour had the highest average protein content of 22.63% while with a temperature of 60 ℃ it had the lowest protein content of 16.25%. Other results also showed that drying with the roasting method could provide a difference in protein content of 18.45%. The decrease in protein levels during the roasting process itself can occur as a result of the protein denaturation process that occurs during the drying process.